Readdressing the role of therapeutic drug monitoring for antiepileptic drugs – A tertiary care hospital experience - Soanker, Radhika; JC Udutha, Shobha; Kumar Rao T, Ramesh (International Journal of Medical Research and Review, 2016)
Background: Therapeutic drug monitoring is a beneficial tool to supervise patients when they do not respond to a therapeutic dose. Inter individual variability in the concentration of an antiepileptic drug that produces optimal therapeutic response is highly significant. Therefore, this retrospective study was taken up to study the inter relation between antiepileptic drug dosages, serum concentration sand clinical condition in the Indian patients. Materials and Methods: This is a retrospective study, in which the data of the samples of adult patients of either gender, analyzed for Phenytoin, Valproate, Carbamazepine and Phenobarbitone were included. The samples were stratified based on dosage prescribed. The endpoints were to estimate the percentage of samples of each stratum having sub therapeutic, therapeutic and supra therapeutic concentrations. Results: Of the 134 samples included, 114 (85%) were analyzed for phenytoin, 9 for valproate, 7 for carbamazepine and 4 for phenobarbitone. Of the 114 samples analyzed for phenytoin, 61(53.5%) samples were having sub therapeutic concentrations, 22 samples (19.3%) had therapeutic concentrations and 31 samples (27.2%) had toxic concentrations. Among the 61 samples having sub therapeutic concentrations, 54.1% were prescribed dose of 300-350mg/day, 16.4% were on 350-400 mg/day and 1.6% were taking above 400mg/day. Of the total cases referred, 41.8 % had H/O of seizures and 30.6% presented with toxic symptoms. Conclusion: This study demonstrated unpredictable inter individual variability in clinical response based on reference ranges. However, the relevance of individual reference concentrations for predicting outcomes can only be confirmed through adequately controlled randomized studies.